2021
DOI: 10.3389/fneur.2021.683094
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Care Planning in Parkinson's Disease: In-depth Interviews With Patients on Experiences and Needs

Abstract: Introduction: Advance care planning (ACP) is an iterative process of discussing the needs, wishes, and preferences of patients regarding disease-specific and end-of-life issues. There is ample evidence that ACP improves the quality of life and promotes the autonomy of patients with cancer and motor neuron disease who have a high disease burden and shortened life expectancy. In Parkinson's disease (PD) though, knowledge about the experiences and preferences of patients regarding ACP is scarce, despite the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The thirteen included studies were published from 2004 to 2021, with one study from 2004 [20] and the remaining twelve studies from 2014 to 2021. There were four studies from the US, [21][22][23][24] two each from the UK, [25,26] Australia [27,28] and the Netherlands, [29,30] and one from each of Sweden, [20] New Zealand, [31] and Canada. [32] Most of the studies reported a specific purpose -e.g., how patients view the role of their GP, [29] or patients' perceptions of a specific exercise [22,27,31] or prevention program, [21] or of their perioperative experiences.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thirteen included studies were published from 2004 to 2021, with one study from 2004 [20] and the remaining twelve studies from 2014 to 2021. There were four studies from the US, [21][22][23][24] two each from the UK, [25,26] Australia [27,28] and the Netherlands, [29,30] and one from each of Sweden, [20] New Zealand, [31] and Canada. [32] Most of the studies reported a specific purpose -e.g., how patients view the role of their GP, [29] or patients' perceptions of a specific exercise [22,27,31] or prevention program, [21] or of their perioperative experiences.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[24] Most of the studies used coding and thematic analyses, though one study applied saliency analysis, [28] one used grounded theory, [27] one used a constant comparative approach for analysis [29] and one a data-driven constant comparative approach. [30] Details of study characteristics are presented in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Kurpershoek et al [38] conducted in-depth interviews with 20 patients with PD to understand their needs and wishes for an early nursing intervention plan. Te results revealed that most people realized that their neurologists mainly focused on drug treatment and had little time to solve their needs for more comprehensive methods of living with Parkinson's disease, indicating that they lacked supportive nursing guidance.…”
Section: A Program For Early Prevention Of Od Complicationsmentioning
confidence: 99%
“…It includes considerations about disease- and symptom-specific treatment, resuscitation and other life-prolonging modalities, treatment restrictions, end-of-life wishes and appointment of surrogate decision-makers ( Walter, Seeber, Willems, & de Visser, 2018 ). ACP is most effective when initiated early, alongside curative therapies, allowing patients, their next-of-kin and caregivers to proactively address the challenges together, and is associated with better quality of life, reduced rates of stress, anxiety and depression and less hospital admissions ( Kurpershoek et al, 2021 ; Walter et al, 2018 ).…”
Section: Specific Palliative Care Needs In People With Parkinson's Di...mentioning
confidence: 99%
“…However, although PwP prefer their health-care professionals to raise the subject of ACP, their desire to discuss advance care preferences ranges from early following the diagnosis to later stages of PD, and it might be challenging for clinicians to ascertain the level of readiness for such discussions ( Kurpershoek et al, 2021 ; Miyasaki & Robinson, 2020 ). For example, neurologists mostly initiate the ACP at the terminal stages of PD ( Walter et al, 2018 ).…”
Section: Specific Palliative Care Needs In People With Parkinson's Di...mentioning
confidence: 99%